2021
DOI: 10.1097/cad.0000000000001169
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic values of prognostic nutritional index in extensive-stage small-cell lung cancer

Abstract: We aimed to assess the prognostic and predictive significance of pretreatment Prognostic Nutritional Index (PNI) in extensive-stage small-cell lung cancer (ES-SCLC) patients treated with first-line chemotherapy. We designed this study to evaluate the prognostic role of PNI in 147 ES-SCLC patients treated with platinum-based combination regimen between 2011 and 2018. Kaplan-Meier survival analyses and Cox proportional hazard models were used to examine the effects of basal PNI on overall survival (OS). The medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…A prior retrospective study showed that low PNI (≤46) was an independent risk factor for poor OS in NSCLC patients [43]. Another study reported that patients with high PNI (≥49.17) had a longer OS than those with low PNI (<49.17) (13 months vs. 12 months, P=0.03) [44]. A study involving 157 NSCLC patients observed the impact of preoperative SII on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A prior retrospective study showed that low PNI (≤46) was an independent risk factor for poor OS in NSCLC patients [43]. Another study reported that patients with high PNI (≥49.17) had a longer OS than those with low PNI (<49.17) (13 months vs. 12 months, P=0.03) [44]. A study involving 157 NSCLC patients observed the impact of preoperative SII on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis demonstrated that patients with high PNI prior to treatment exhibited a longer OS, disease-free survival/relapse-free survival and PFS ( 21 ). In addition, a previous study revealed that PNI exhibited potential in predicting the OS of patients with extended-stage SCLC following first-line treatment ( 22 ). Tumor shrinkage is a relatively common prognostic indicator in chemotherapy, but it is not often used in the context of novel treatment options, such as immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the outcome of cancer patients is determined by many factors, including nutrition status [ 5 ] and anticancer immunity [ 6 ], in addition to the cancer cells themselves; accordingly, it is plausible that prognostic markers could be more reasonable if these factors are comprehensively considered. The prognostic nutritional index (PNI), which is a marker calculated based on serum albumin and lymphocytes, is a robust prognostic indicator in many malignancies, including lung cancer [ 7 ], nasopharyngeal cancer [ 8 ], liver cancer [ 9 ], breast cancer [ 10 ], gastric cancer [ 11 ] and CRC [ 12 , 13 ]. Interestingly, previous studies have indicated that the prognostic efficacy of PNI was superior to that of other inflammation-based prognostic indicators [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%